2008
DOI: 10.1364/ol.33.000264
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic dielectric surfaces as new low-loss light-matter interfaces

Abstract: We propose a new mirror architecture, which is solely based upon structuring of the surface of a monolithic, possibly monocrystalline, bulk material. We found that a structure of T-shaped ridges of a subwavelength grating can theoretically provide 100% reflectivity. Since no material needs to be added to the mirror device, lowest mechanical loss can also be expected. [5,6] this interface needs to provide outstanding low optical and mechanical losses. High reflectivity is demanded as lost photons result in dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…However, Bunkowski et al [19] theoretically investigated such a device and found parameters for a high-reflection waveguide mirror with broad spectral response. Recent theoretical research showed that even the remaining high-index layer can be avoided and that a monolithic high-reflection mirror is possible by applying an appropriate grating structure to the substrate's surface without the need for adding any other material [20]. This new approach does not imply suspended microstructures [21], which had been reported before and, therefore, overcomes the limitation to very small grating areas.…”
Section: Introductionmentioning
confidence: 90%
“…However, Bunkowski et al [19] theoretically investigated such a device and found parameters for a high-reflection waveguide mirror with broad spectral response. Recent theoretical research showed that even the remaining high-index layer can be avoided and that a monolithic high-reflection mirror is possible by applying an appropriate grating structure to the substrate's surface without the need for adding any other material [20]. This new approach does not imply suspended microstructures [21], which had been reported before and, therefore, overcomes the limitation to very small grating areas.…”
Section: Introductionmentioning
confidence: 90%
“…These include diffractively-coupled mirrors [81,82], the use of corner reflectors [83], or the use of waveguide (macro-structured) surfaces [84,85]. These coating-free solutions still require significant development.…”
Section: Coating-free Mirrorsmentioning
confidence: 99%
“…This property is, for instance, widely investigated for use in narrowband filter applications [21]. However, broadband designs under normal incidence as investigated in [10,11,22,23] are favourable for the purpose of highly reflective surface mirrors in high-precision interferometric experiments, since they are less sensitive to parameter deviations. The basic principle of a waveguide grating mirror under normal incidence is shown in Fig.…”
Section: Waveguide Grating Mirrors Under Normal Incidencementioning
confidence: 99%